The prevalence of pseudoscientific ideas and neuromyths among sports coaches - Bailey, R.; Madigan, D. J.; Cope, E.; Nicholls, A. R. (Frontiers in Psychology, 2018)
There has been an exponential growth in research examining the neurological basis of human cognition and learning. Little is known, however, about the extent to which sports coaches are aware of these advances. Consequently, the aim of the present study was to examine the prevalence of pseudoscientific ideas among British and Irish sports coaches. In total, 545 coaches from the United Kingdom and Ireland completed a measure that included questions about how evidence-based theories of the brain might enhance coaching and learning, how they were exposed to these different theories, and their awareness of neuromyths. Results revealed that the coaches believed that an enhanced understanding of the brain helped with their planning and delivery of sports sessions. Goal-setting was the most frequently used strategy. Interestingly, 41.6% of the coaches agreed with statements that promoted neuromyths. The most prevalent neuromyth was "individuals learn better when they receive information in their preferred learning style (e.g., auditory, visual, or kinesthetic)", which 62% of coaches believed. It is apparent that a relatively large percentage of coaches base aspects of their coaching practice on neuromyths and other pseudoscientific ideas. Strategies for addressing this situation are briefly discussed and include changing the content of coach education programs.